Uptake and Response of Maize (Zea mays L.) Varieties to Nitrogen and Phosphorus Fertilizers in Semi-arid Areas of Eastern Ethiopia - Hassen Abdulahi; Ed Sarobol; Vichan Vichukit; Chairerk Suwannarat (Agriculture and Natural Resources, 2006)
A field experiment was conducted on two locations of semi-arid areas of Eastern Ethiopia during the rainy seasons of 2003 and 2004. The objective of this study was to determine grain yield and N and P contents and uptakes of maize (Zea mays L.) varieties in semi-arid areas of Eastern Ethiopia. The experiment was conducted with factorial combinations of three levels of N (0, 41 and 64 kg N/ha), three levels of P (0, 46 and 69 kg P2O5/ha) and two maize varieties laid out in a Randomized Complete Block Design with three replications. Analysis of variance revealed significant differences due to the different levels of applied N for almost all of the yield and agronomic parameters studied, where P fertilizer had a significant effect only on stover biomass and grain yield. Interaction effect of N and P on grain yield was significant. Among all of the N and P treatment combinations, maximum grain yield of maize 3868 kg/ha in Babile and 5069 kg/ha in Dire Dawa were obtained with the application of 64 kg N/ha and 46 kg P2O5/ha in both locations. Melkassa I recorded the highest value for yield and other parameters, where local variety showed the least value for yield in both locations. Nitrogen and phosphorus concentrations and uptakes in the maize varieties increased with increasing levels of N and P fertilizers. Compared with the control concentration of N in the maize plant of both varieties, it increased up to the highest levels of N application, indicating possible improvement in the crude protein content of the maize grains. Generally, application of N enhanced uptakes and concentrations of N and P nutrients in the maize tissues than P fertilizer applied. Total plant N and P uptakes by the above ground parts of both varieties in both locations, the sum of uptake by grain yield and stover in kg/ha, increased relatively at the rates of 0 and 64 kg N/ha and 0 and 69 kg P2O5/ha, respectively. Efficiency in N fertilizer was calculated for Melkassa I and Local maize varieties in both locations and Melkassa I variety had a higher efficiency of N fertilizer than the local maize variety in both locations, indicating that Melkassa I produced much more grain and was thus more efficient in converting fertilizer nitrogen in to grain.